Postoperative Pseudomeningocele: A Rare Complication of Lumbar Spine Surgery - Tushar Kalekar; Niharika Prasad; Bhavya Dang (Journal of Clinical and Diagnostic Research)
A 64-year-old male with a history of chronic lower back pain for the past three years, which had progressively worsened over the preceding month and led to difficulty in walking, presented with associated tingling sensations in the left lower limb for two years and urinary incontinence for one week. He was evaluated clinically and radiologically and diagnosed with multilevel lumbar canal stenosis and degenerative spondylolisthesis. There was no history of trauma, fever, constitutional symptoms, or bowel disturbances. The patient was known to be hypertensive, non diabetic and a non smoker and had no prior history of spinal trauma or tuberculosis.